ANÁLISE DE LIVRO DE PORTUGUÊS EM CONTEXTO ESTRANGEIRO SOB A ÓTICA DO INTERACIONISMO SOCIODISCURSIVO - Strukoski, Eleticia Elza Carneiro Podolak (2018)
This research aims to perform an analysis of the activities of a Portuguese textbook chapter, used in a foreign context, under the theoretical perspective of sociodiscursive interactionism (ISD) and the teaching of Portuguese as a foreign language (PFL). To carry out this analysis, there are four research objectives: I) to carry out a survey of the objectives presented at the beginning of the teacher's material in chapter 13 of the book "Portuguese Language" and to verify if they were achieved through the activities proposed in both the student's book and in the referrals of the teacher's book; II) to verify if the teachable dimensions of the textual genre "wonderful tales" are approached in the course of the activities of the chapter; III) to establish relationships with didactic material and teaching practice through a written reflective journal; and IV) to establish relationships between the teaching practice, through the class journal reports, and the specificities of the PFL teaching. As a theoretical basis, we use the studies of George Herbert Mead (1967) and Vygotsky (1991, 1993) from the perspective of Social Interactionism; Bronckart (2006a; 2006b; 2007a; 2007b; 2010) on Socio-discursive Interactionism; Dolz and Schneuwly (1999; 2004), Schneuwly and Dolz (2013) and Schneuwly (2013), on language teaching, Cristovão and Stutz (2011) on language capacities studies, Stutz (2012) on reflexive diaries; Coracini (1999) and Mendes (2006) regarding textbooks and, finally, regarding the teaching of PFL, we use Almeida Filho (2012), Furtoso and Riveira (2013), Zoppi Fontana 2010), Carvalho (2012), Valdéz (2005) and Batista and Alarcón (2012). We use the qualitative approach of applied nature, with quantitative stretches for enumeration of activities in certain prisms. We also characterized it as a documentary, using authentic documents as a database for analysis and action research, as I, as a researcher, teacher of the analyzed textbook and writer of the reflective journal, actively participated in research in the search for resolution of a collective situation in which I am involved. This research has as context an immersion program in Portuguese language, in the state of Utah, United States. As the book is divided into three copies: a) the student activity book, b) the textbook, c) the teacher's book, we will analyze the latter, because it unites the three copies in one. We will also analyze six reports of the reflective journal I wrote, which are related to the classes of the analyzed chapter, focusing on the expansion of the language capacities (CL) by the students and and the specificities of the PFL teaching. Our results demonstrate that the book "Portuguese Language" fulfills all the objectives it proposes, either implicitly or explicitly, although it presents divergences with respect to ISD and teaching of PFL. We consider that the book presented an insufficient approach regarding work with textual genres, since it does not bring explicit activities to the students and few explicit orientations to teachers in teachable dimensions as mechanisms of textualization and context of production of the genre, leaving a gap to be filled by practice which may or may not happen in order to address these dimensions. We have identified in the journal accounts, the expansion of language capacities in specific operations, action capacities, discursive capacities, linguistic-discursive capacities, and signification capacities. However, we realized that much of this enlargement was due to the teacher's practice, not necessarily through the book's directions and activities. Regarding the specificities of PFL teaching, the book presents significant gaps regarding the work with orality and cultural aspects of the Portuguese language. In light of these considerations, we conclude that the material, despite fulfilling its objectives and bringing an authentic example of the genre, needs to be reformulated so that it can contemplate in a broader and more explicit way the teachable dimensions of the textual genre that is proposed, as well as to present more consistent activities and approaches with the teaching of PFL.